The Case of Jamal Khashoggi and the Right to Life - Balcı, Murat; Çakır, Kerim (Sakarya Üniversitesi, 2025)
The right to life imposes two main responsibilities on states. On one hand, states are charged with a negative obligation, which implies that states shall refrain from violating the right to life of the people in their territories. On the other hand, states have the positive obligation to ensure effective security that allows people to enjoy their right to life. In other words, states are obligated to protect the people in their territory from fatal acts of aggression. Türkiye’s handing of the Khashoggi case over to Saudi Arabia raised the argument that, as a party to the European Convention on Human Rights (ECHR), it had violated the right to life by acting against procedural obligations in the case of the murder of Jamal Khashoggi. This study will briefly discuss the right to life and how states protect it and then examine whether Türkiye and Saudi Arabia had violated Khashoggi’s right to life by acting against their procedural obligations regarding investigations and prosecutions that had taken place in Türkiye and Saudi Arabia by Türkiye transferring the Khashoggi case to Saudi Arabia after Jamal Khashoggi’s murder.
Keywords: Jamal Khashoggi; Right to Life; Positive Procedural Obligation; Efficient Investigation; Transfer of Proceedings